The interstellar extinction in the open clusters Tr 14, Tr 15, Tr 16/Cr 232 and Cr 228 in NGC 3372 : New near-infrared photometry - Tapia, Mauricio (1988)
Near-infrared JHKL photometry of more than 200 stars, members of the open clusters Tr 14, Tr 15, Tr 16, Cr 228 and Cr 232 in the Carina Nebula are presented. From comparing these results with the available visual photometry and spectroscopy, it is found that, except in Tr 15, the intracluster reddening is characterized by a ‘normal’ extinction law at λ>0.5μm but is highly anomalous and variable in the U- and B-bands. This behaviour may be explained by the presence of intracluster interstellar grains ‘processed’ by shock waves presumably associated with the explosive history of ƞ Carinae. All clusters are found to be at the same distance from the Sun at d=2.4±0.2kpcorV0−Mv=11.9±0.2⁠. The total amount of reddening, though, differs significantly from cluster to cluster.